Land use dynamics in a tropical protected area buffer zone: is the management plan helping? - de Souza, Juliana Carmo [UNESP]; Mendes, Tatiana Sussel Gonçalves [UNESP]; Bignotto, Rafael Beltrame; de Alcântara, Enner Herenio [UNESP]; Massi, Klécia Gili [UNESP] (Springer Nature, 2024)
Buffer zones, mandatory in the Brazilian protected area network as well as globally common in reserves, are essentially transitional areas within the core protected area (PA) that aim to downgrade the land-use intensity of the surrounding landscape from potentially damaging external influences. Buffer zones are regulated by the management plan and studies comparing these restrictions to land cover dynamics, and landscape configuration in buffer zones of protected areas are not common. Thus, we aimed to assess land use and land cover dynamics since 1995 in the buffer zone of Serra do Mar State Park (in Portuguese: Parque Estadual Serra do Mar: PESM), Southeast Brazil, and to compare them with restrictions imposed by its Management Plan. We hypothesized that, despite restrictions of the management plan, land use and land cover changes have intensified and increased in extent, in the nearest surroundings of PESM, with regards to deforestation, urban expansion, and forest discontinuity, which may further result in threatening conservation values of PESM. To evaluate land use and land cover dynamics in the study site, transition satellite imagery from 1995 to 2020 available at MapBiomas Project was used. We verified that (i) forest cover percentages in the whole area, in each municipality and in legal reserves inside private rural land in the PESM buffer zone did not alter, (ii) the rate at which urban areas expanded during the study period slowed over time, and (iii) the boundary between the protected area and the buffer zone was mostly deforested. Thus, the PESM Management plan and restrictions, together with other environmental policies not analyzed in this study, might be working to contain deforestation and urbanization, and, lately, to maintain conservation values of PESM. However, there is a need for alternatives to improve the implementation of regulations on the buffer zone management plan.
Keywords: Atlantic forest; Conservation; Forest cover; Protected area; Urban expansion